DNA hypomethylation and aberrant expression of the human endogenous retrovirus ERVWE1/syncytin-1 in seminomas - Benešová, Martina; Trejbalová, Kateřina; Kovářová, Denisa; Vernerová, Zdenka; Hron, Tomáš; Kučerová, Dana; Hejnar, Jiří (Retrovirology, 2017)
BACKGROUND: Syncytin-1 and 2, human fusogenic glycoproteins encoded by the env genes of the endogenous retroviral loci ERVWE1 and ERVFRDE1, respectively, contribute to the differentiation of multinucleated syncytiotrophoblast in chorionic villi. In non-trophoblastic cells, however, the expression of syncytins has to be suppressed to avoid potential pathogenic effects. Previously, we have shown that the transcriptional suppression of ERVWE1 promoter is controlled epigenetically by DNA methylation and chromatin modifications. In this study, we describe the aberrant expression of syncytin-1 in biopsies of testicular germ cell tumors. RESULTS: We found efficient expression and splicing of syncytin-1 in seminomas and mixed germ cell tumors with seminoma component. Although another fusogenic gene, syncytin-2 was also derepressed in seminomas, its expression was significantly lower than that of syncytin-1. Neither the transcription factor GCM1 nor the increased copy number of ERVWE1 were sufficient for this aberrant expression of syncytin-1 in seminomas. In accordance with our recent finding of the highly increased expression of TET1 dioxygenase in most seminomas, the ERVWE1 promoter was significantly hypomethylated in comparison with the matched controls. In contrast, 5-hydroxymethylcytosine levels were not detectable at the ERVWE1 promoter. We further describe that another endogenous retroviral element adjacent to ERVWE1 remains transcriptionally suppressed and two additional HERV-W family members are only slightly upregulated in seminomas. CONCLUSIONS: We conclude that DNA demethylation of the ERVWE1 promoter in seminomas is a prerequisite for syncytin-1 derepression. We propose the spliced syncytin-1 expression as a marker of seminoma and suggest that aberrant expression of endogenous retroviruses might be a correlate of the hypomethylated genome of seminomas.
Keywords: RNA splicing; DNA, Viral; Seminoma; DNA virů; lidé; Gene Expression Regulation; Endogenous Retroviruses; Transcription; Human endogenous retrovirus; endogenní retroviry; Pregnancy Proteins; těhotenské proteiny; Promoter DNA methylation; ERVWE1; genové produkty env; Humans; Gene Products, env; testikulární nádory; epigeneze genetická; mužské pohlaví; seminom; Germ cell tumor; Epigenesis, Genetic; Male; Testicular Neoplasms; regulace genové exprese; 5-Hydroxymethylcytosine; DNA Methylation; metylace DNA